Effects of swimming training on bone mass and the GH/IGF-1 axis in diabetic rats - Gomes, R. J.; de Mello, M. A. R.; Caetano, F. H.; Sibuya, C. Y.; Anaruma, Carlos Alberto [UNESP]; Rogatto, G. P.; Pauli, J. R.; Luciano, E. (Churchill Livingstone, 2006)
The aim of this study was to examine the influence of moderate swimming training on the GH/IGF-1 growth axis and tibial mass in diabetic rats. Male Wistar rats were allocated to one of four groups: sedentary control (SC), trained control (TC), sedentary diabetic (SD) and trained diabetic (TD). Diabetes was induced with alloxan (35 mg/kg b.w.). The training program consisted of a 1 h swimming session/day with a load corresponding to 5% of the b.w., five days/week for six weeks. At the end of the training period, the rats were sacrificed and blood was collected for quantification of the serum glucose, insulin, GH, and IGF-1 concentrations. Samples of skeletal muscle were used to quantify the IGF-1 pepticle content. The tibias were collected to determine their total area, length and bone mineral content. The results were analyzed by ANOVA with P < 0.05 indicating significance. Diabetes decreased the serum levels of GH and IGF-1, as well as the tibial length, total area and bone mineral content in the SD group (P < 0.05). Physical training increased the serum IGF-1 level in the TC and TD groups when compared to the sedentary groups (SC and SD), and the tibial length, total area and bone mineral content were higher in the TD group than in the SD group (P < 0.05). Exercise did not alter the level of IGF-1 in gastrocnemius muscle in nondiabetic rats, but the muscle IGF-1 content was higher in the TD group than in the SD group. These results indicate that swimming training stimulates bone mass and the GH/IGF-1 axis in diabetic rats. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: bone mass; diabetes mellitus; insulin-like growth factor (IGF-1); training